Composite TiO2-based photocatalyst with enhanced performance - Muzikova, Barbora; Martiniakova, Ivana; Mikyskova, Eliska; Mergl, Martin; Kalbac, Martin; Zouzelka, Radek; Rathousky, Jiri (Photochemical & photobiological sciences, 2023)
TiO2 is the most studied photocatalyst because of its non-toxicity, chemical stability, and low cost. However, the problem of TiO2 is its low activity in the visible region of the spectrum. In this study, we focused on the preparation of composite photocatalytic materials with altered light absorption properties. TiO2 P25 and various metal oxides were mechanically joined by ball-milling and immobilized on glass plates. The prepared samples were evaluated based on their ability to degrade NO in gas phase. The formation of undesirable byproducts was also investigated. Four best performing composites were later chosen, characterized, and further evaluated under various conditions. According to their performance, the metal oxide additives can be divided into three groups. P25/Fe2O3 showed the most promising results-an increase in overall deNOx activity under modified ISO conditions and altered selectivity (less NO2 is formed) under both simulated outdoor and simulated indoor conditions. On the other hand, P25/V2O5 composite showed negligible photocatalytic activity. The intermediate group includes P25/WO3 and P25/ZnO photocatalysts, whose performances are similar to those of pristine P25.
Keywords: katalýza; Catalysis; oxidy; titan; Oxides; Titanium